MANAJEMEN RISIKO DALAM PROSES ESTIMASI BIAYA PADA PROYEK KONSTRUKSI GEDUNG BERTINGKAT DI KOTA DENPASAR - Ida Ayu Praniti Tresna Putri; I N. Norken; I B. Rai Adnyana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2016)
Abstract : On the implementation of the construction project, financing is the main consideration due to the number of large and vulnerable to various risks. Cost control is the beginning of the estimates. An inaccurate estimation could have a negative impact on the whole process of construction. Because of estimation is reference in preparing the budget and used as control of the cost of projects, then required to major risk analysis that can be used as a basis in the mitigation. This research was conducted with qualitative descriptive method by interviews and survey. Data was collected by distributing questionnaires to the respondents using purposive sampling method, which simply selecting respondents who were competent and expert about the possible risks. The number of respondents was 25 who represent 8 construction project belonging to the government which is located in Denpasar. The results showed that there were 40 risks identified, from literature identified 16 risks and from brainstorming identified 24 risks. Than from 40 risks there are 34 major risks which was 9 risks classified as unacceptable and 25 risks classified as undesirable. Most dominant risks were the risks of estimator team and project. There were 16 mitigation measures at an unacceptable risk and 41 mitigitation measures at an undesirable risk. Most dominant risks were the risks of contractors and owner.